Centrality dependence of pion freeze-out radii in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (Physical review, 2016)
We report on the measurement of freeze-out radii for pairs of identical-charge pions measured in Pb-Pb collisions at √sNN=2.76 TeV as a function of collision centrality and the average transverse momentum of the pair kT. Three-dimensional sizes of the system (femtoscopic radii), as well as direction-averaged one-dimensional radii are extracted. The radii decrease with kT, following a power-law behavior. This is qualitatively consistent with expectations from a collectively expanding system, produced in hydrodynamic calculations. The radii also scale linearly with ⟨dNch/dη⟩1/3. This behavior is compared to world data on femtoscopic radii in heavy-ion collisions. While the dependence is qualitatively similar to results at smaller √sNN, a decrease in the ratio Rout/Rside is seen, which is in qualitative agreement with a specific prediction from hydrodynamic models: a change from inside-out to outside-in freeze-out configuration. The results provide further evidence for the production of a collective, strongly coupled system in heavy-ion collisions at the CERN Large Hadron Collider.
Im Titel stehen der Ausdruck "sNN" unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, Y. Wang, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 964 weitere]
Gesehen am 28.07.2020